The role and mechanism of 5-HTDRN-BNST neural circuit in anxiety and fear lesions - Zheng, Xianli; Dingpeng, Li; Yan, Xingke; Yao, Xiaoqiang; Wang, Yongrui (Frontiers in Neuroscience, 2024)
Central 5-hydroxytryptaminergic dorsal raphe nucleus (5-HTDRN)-bed nucleus of stria terminalis (BNST) neural circuit dysfunction is one of the important neurobiological basis of anxiety and fear disorders. Under stress, 5-hydroxytryptamine (5-HT) neurons act on BNST receptors to attenuate anxiety and fear responses or enhance anxiety and fear. In BNST, corticotropin releasing factor neurons play a role in regulating emotions by reversely regulating excitatory or inhibitory 5-HT neurons. The composition of 5-HTDRN-BNST neural circuit, the pathological changes of 5-HTDRN-BNST neural circuit function damage under stress, and the effects of 5-HTDRN-BNST neural circuit on anxiety disorder, panic disorder and post-traumatic stress disorder were analyzed and are summarized in this paper. The characteristics of functional changes of the neural circuit and its effects on brain functional activities provide a basis and ideas for the treatment of anxiety and fear disorders through the regulation of 5-HTDRN-BNST neural circuit, and they also provide a new perspective for understanding the pathological mechanism of such diseases.When the body is transiently or continuously exposed to trauma and acute stress, people will experience a variety of negative emotions such as fear, anxiety, and depression. Most of these risk factors are classified as exposure to traumatic events. These emotions are mainly due to the central